Aldosterone – underestimated link in the pathogenesis of arterial hypertension - Kosicka, Teresa; Kara-Perz, Hanna; Głuszewski, Wojciech; Perz, Stanisław (Przewodnik Lekarza/Guide for GPs, 2005)
Lately numerous investigations have denied the thesis that primary aldosteronism (PA) is a rare disease. Now PA is regarded as probably the most common cause of secondary arterial hypertension. Careful investigation of the patient with drug-resistant arterial hypertension is required in order to verify the diagnosis of PA. In this paper causes, signs and diagnostic criteria of PA were shortly described. The diagnostic value of aldosterone-renin ratio was emphasized. This index is very useful in early phase of PA in patients without typical signs, with normal serum kalium concentration and with severe hypertension requiring multi-drug medication. Reaching the diagnosis of PA and its specific treatment will make many patients recover, while now they are regarded as cases resistant to antihypertensive therapy.